2015
DOI: 10.1002/adma.201500417
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme‐Responsive Delivery of Multiple Proteins with Spatiotemporal Control

Abstract: The growth of tissues and organs is regulated by orchestrated signals from biomolecules such as enzymes and growth factors. The ability to deliver signal molecules in response to particular biological events (e.g., enzyme expression and activation) holds great promise towards tissue healing and regeneration. The current delivery vehicles mainly rely on hydrolysable scaffolds and thin films of protein-containing polymers, which cannot be programmed to respond to biological signals. We report herein an injectabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 22 publications
0
68
0
Order By: Relevance
“…Cell-loaded hydrogels provide structural support that not only directly promote the survival of encapsulated cells [6], but also promote cell infiltration from the surrounding parenchyma [7] and reduce the glial scar and inflammation at the ischemic border [8, 9]. Similarly, local drug delivery from injectable hydrogels can achieve sustained [3, 10, 11] or sequential delivery [12] in a time- and space-controlled manner, while enhancing protein stability, diffusion distance and in vivo bioactivity [11]. Polymer-based hydrogels are highly customizable as their composition can be modified to adapt to the host tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Cell-loaded hydrogels provide structural support that not only directly promote the survival of encapsulated cells [6], but also promote cell infiltration from the surrounding parenchyma [7] and reduce the glial scar and inflammation at the ischemic border [8, 9]. Similarly, local drug delivery from injectable hydrogels can achieve sustained [3, 10, 11] or sequential delivery [12] in a time- and space-controlled manner, while enhancing protein stability, diffusion distance and in vivo bioactivity [11]. Polymer-based hydrogels are highly customizable as their composition can be modified to adapt to the host tissue.…”
Section: Introductionmentioning
confidence: 99%
“…The D -chiral enantiomer has lower degradation kinetics compared to the L -chiral peptide 15,18 ; thus, n(VEGF) synthesized with an increasing D -chiral peptide content will have a slower degradation rate, and thereby a slower release rate of VEGF. 33 The selection of this plasmin-sensitive peptide sequence as the crosslinker is such that VEGF can be released when proteolytic and fibrinolytic proteases are present from endothelial cells (Fig. 1b).…”
Section: Resultsmentioning
confidence: 99%
“…The release rate from nanocapsules in this damaged environment can be inferred in a similar study, where we demonstrated 100 ng of n(Protein) 100% was mostly released by day 3 and 100 ng of n(Protein) 25% was mostly released from day 3 to day 6. 33 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VEGF was encapsulated within protease-labile, water-soluble nanocapsules formed through radical polymerization of acrylate-modified peptides (release rate is controlled through mixing L and D crosslinking peptides). We demonstrated that controlled release in vivo is associated with improved vascularization within the stroke peri-infarct and infarct regions [41]. …”
Section: Introductionmentioning
confidence: 99%